Grasping an Ought. Adolf Reinach’s Ontology and Epistemology of Legal and Moral Oughts - Passerini Glazel, Lorenzo (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
We almost every day direct our actions with reference to social, moral or legal norms and oughts. However, oughts and norms cannot be perceived through the senses: how can we “grasp” them, then? Adolf Reinach distinguishes enacted norms and oughts created through a social act of enactment, from moral norms and oughts existing in themselves independently of any act, knowledge or experience. I argue that this distinction is not a distinction between two species of oughts within a common genus: it is rather a deeper ontological distinction between two modes of existence that are quite different, even though both are objective, according to Reinach. This ontological distinction is reflected in the way in which enacted oughts and moral oughts can be grasped, respectively: in the former case, the enacted ought is grasped by going back to the underlying social act from which it springs; in the latter, a “grasping through feeling” (fühlende Erfassen) of the moral values is implied.